Creating Genderfair Schools and Classrooms : Engendering Social Justice for 5 to 13 Year Olds. - Reed, Lynn Raphael (Lucky Duck Books., 2007)
For many teachers, gender issues related to role models, image and expectations have an effect upon the behaviour and achievement of both boys and girls, often to their disadvantage. This innovative and practical resource, for teachers of students aged 14-19provides: - a programme to promote gender equality and inclusivity in schools and colleges - a rationale for the programme based on social justice - a practical set of classroom activities to implement the programme. The book adopts an 'action inquiry' methodology - engaging students and staff in the processes of investigating what is curre.